Magic, Inherent Evil, and the Proto-feminism of María de Zayas y Sotomayor: A Comparison with Selected novelas of Miguel de Cervantes and Alonso de Castillo Solórzano - Manley, Stewart (Liverpool University Press, 2019)
This article compares the portrayal of women who use magic in seventeenth-century novelas of María de Zayas y Sotomayor with novelas by Miguel de Cervantes Saavedra and Alonso de Castillo Solórzano to illuminate the complexity and uniqueness of Zayas's proto-feminism. The article suggests that Zayas provides a nuanced portrayal of these women that departs only partially from the prevailing paradigm reflected in Cervantes's and Solórzano's more conventional representations. A restrained approach that blames both men and women for evil arguably permitted Zayas's work to be published in the censorial environment of her time. Examining who uses magic, how they are described, and the purposes and consequences of its use, is useful in understanding gender portrayal, as well as how Zayas's work differs from her contemporaries' and what that difference means for her incipient feminist ideals. Scholars have noted the ambiguous nature of Zayas's feminism and some have examined her portrayals of the supernatural, but none has conducted a detailed textual comparison integrating these subjects. © 2019 Liverpool University Press.All Rights Reserved.